2019
DOI: 10.3390/w11020243
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Spatiotemporal Variability of Evapotranspiration and Its Governing Factors in a Mountainous Watershed

Abstract: Evapotranspiration (ET) is a key component of the water balance, which influences hydrometeorology, water resources, carbon and other biogeochemical cycles, and ecosystem diversity. This study aims to investigate the spatio-temporal variations of ET at the East River watershed in Colorado and analyze the factors that control these variations. ET was acquired using the community land model (CLM) simulations and was compared with the values estimated using Fu’s equation and a watershed-scale water balance equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 26 publications
(24 reference statements)
1
33
4
Order By: Relevance
“…This is higher than basin‐wide ER estimates by Tran et al () at 550 mm/year for elevations 2,950 to 3,200 m and 300 mm/year at higher elevations. However, our inclusion of snow redistribution as well as lateral flow and groundwater to subsidize ET is not accounted for by Tran et al () and may explain differences in results. With reasonable water budget components, we can move toward answering questions pertaining to groundwater.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This is higher than basin‐wide ER estimates by Tran et al () at 550 mm/year for elevations 2,950 to 3,200 m and 300 mm/year at higher elevations. However, our inclusion of snow redistribution as well as lateral flow and groundwater to subsidize ET is not accounted for by Tran et al () and may explain differences in results. With reasonable water budget components, we can move toward answering questions pertaining to groundwater.…”
Section: Discussioncontrasting
confidence: 56%
“…We estimate total average annual ET losses in CC at 623±50 mm/year. This is higher than basin-wide ER estimates by Tran et al (2019) at 550 mm/year for elevations 2,950 to 3,200 m and 300 mm/year at higher elevations. However, our inclusion of snow redistribution as well as lateral flow and groundwater to subsidize ET is not accounted for by Tran et al (2019) and may explain differences in results.…”
Section: Resultsmentioning
confidence: 54%
“…The underlying soil along the hillslope was relatively drier, reflecting efficient evapotranspiration and lack of deep infiltration during summer. As noted earlier, the CLM-based calculations (Tran et al, 2019) for the summer months (WY2016, 2017, 2018) predicted that ET was large enough to prevent net infiltration of monsoon precipitation at this site. Although not part of the hillslope, the floodplain station PLM4 is included for contrast, with its higher water contents and potentials resulting from a shallow depth to the water table (0.76 m bgs during sampling) and higher clay content.…”
Section: Soil Water Contents and Potentials In Late Summersupporting
confidence: 55%
“…(b) Monthly water content of snow and monsoon rainfall (CREST4). (c) Daily and cumulative ET calculated with the CML (Tran et al, 2019).…”
Section: Water Resources Researchmentioning
confidence: 99%
“…Long-term scPDSI anomaly variation in the YZR basin was strong negatively correlated with DTR, by a correlation coefficient of −0.70 in the original time series (Figure 9a). Some studies concluded that changes of PET were dominated by temperature variables [104][105][106]. Although DTR is an important indicator of temperature, it showed a non-significantly correlation with changes of PET in the YZR basin as their correlation coefficient was only 0.36.…”
Section: Multi-scale Response To Climate Changementioning
confidence: 99%